Eksistensi dan Pengembangan Kurikulum Madrasah Aliyah Program Keagamaan (MAPK) MAN 1 Surakarta - Munif Rofi’atur Rohmah; Zainal Arifin (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2017)
Abstract This article discusses the existence and curriculum development of MAPK MAN 1 Surakarta. This research is qualitative research. Research data through observation, in-depth interviews and documentation. The result of this research shows, first, MAPK MAN 1 Surakarta still exist until now (1) support from various parties such as madrasah leaders, MAPK managers and dormitories as well as alumni support, (2) the developed curriculum has successfully delivered quality Islamic Education, (3) the name of MAPK is still used as marketing, (4) the desire to exist, (5) the opening of international class, (6) still needed the graduates who master of Islamic Studies, (7) successful student achievement, (8) the spirit of student have ability to speak Arabic and English. Second, the curriculum development of MAPK MAN 1 Surakarta includes: diagnostic needs, educational objectives, curriculum 2013, tutorial and boarding school activities, learning experiences, and evaluation.